2022
DOI: 10.3390/ma15041316
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Thermomechanical Properties of Poly(lactic acid) via Reduced Graphene Oxide and Bioderived Poly(decamethylene 2,5-furandicarboxylate)

Abstract: Polylactide (PLA) is the most widely used biopolymer, but its poor ductility and scarce gas barrier properties limit its applications in the packaging field. In this work, for the first time, the properties of PLA solvent-cast films are improved by the addition of a second biopolymer, i.e., poly(decamethylene 2,5-furandicarboxylate) (PDeF), added in a weight fraction of 10 wt%, and a carbon-based nanofiller, i.e., reduced graphene oxide (rGO), added in concentrations of 0.25–2 phr. PLA and PDeF are immiscible,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Our group has recently carried out a detailed investigation on PLA/PAF blends prepared via solution mixing, for the production of bioderived films [ 32 , 33 , 34 , 35 , 36 ] and fibers [ 37 , 38 , 39 ]. That work involved blending PLA not only with PBF, but also with longer-alkyl-chain PAFs such as poly(pentamethylene furanoate) (PPeF), poly(hexamethylene furanoate) (PHF), poly(octamethylene furanoate) (POF), poly(decamethylene furanoate) (PDeF), and poly(dodecamethylene furanoate) (PDoF).…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently carried out a detailed investigation on PLA/PAF blends prepared via solution mixing, for the production of bioderived films [ 32 , 33 , 34 , 35 , 36 ] and fibers [ 37 , 38 , 39 ]. That work involved blending PLA not only with PBF, but also with longer-alkyl-chain PAFs such as poly(pentamethylene furanoate) (PPeF), poly(hexamethylene furanoate) (PHF), poly(octamethylene furanoate) (POF), poly(decamethylene furanoate) (PDeF), and poly(dodecamethylene furanoate) (PDoF).…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently performed a thorough investigation on the physical-mechanical properties of PLA/PAF blends prepared via solution mixing, for the development of bioderived films [ 36 , 37 , 38 , 39 , 40 ] and fibers [ 41 , 42 , 43 ], involving not only PBF but also longer-alkyl-chain PAFs such as poly(pentamethylene furanoate) (PPeF), poly(hexamethylene furanoate) (PHF), poly(octamethylene furanoate) (POF), poly(decamethylene furanoate) (PDeF), and poly(dodecamethylene furanoate) (PDoF). These works have confirmed that a small fraction of such PAFs can considerably enhance the strain at break and the fracture toughness of neat PLA.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the sustainable character, as well as the good barrier and mechanical properties of FDCA-based polyesters, the number of reports in the literature concerning their blends with PLA is increasing [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In our previous work, we prepared blends with PLA and PEF, poly(propylene 2,5-furan dicarboxylate) (PPF), or poly(butylene 2,5-furan dicarboxylate (PBF) using solution casting [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%